Ethnic Identity: A Study of Construct Equivalence - Augustinus Supratiknya (Jurnal Psikologi, 2019)
This research aimed to examine the Multigroup Ethnic Identity Measure’s (MEIM 1992) adequacy to explore Indonesian youth’s ethnic identity. Hence MEIM 1992 was adapted into MEIM Indonesia through translation-back-translation method. Involving 448 (179 or 40% male and 269 or 60% female) students aged 17 – 28 years (Mean = 19.87; SD = 1.30) with different ethnic backgrounds in a private university in Yogyakarta as respondents, EFA with SPSS showed that the MEIM Indonesia measured one factor as MEIM 1992 does, CFA with R- studio showed that the one factor model fitted the data (factor loadings ranged from 0.323 to 0.750), its items had r it -s that ranged from 0.32 to 0.64, as a scale had a Cronbach’s alpha of 0.84, showed a concurrent validity coefficient r =0.23 (p < 0.01) with the RSeS Indonesia as a criterion, and was able to differentiate the levels of ethnic identity of sample pairs of Javanese, Bataks, Dayaks, Chinese, Florinese and a mixture of two or three ethnic groups. Hence, the MEIM Indonesia was conceptually and empirically proven to have construct equivalence with the 1992 MEIM as well as to show adequacy and was coined Skala Identitas Suku Bangsa (SISB).